An Assessment of Abu Tammâm's Work Titled B?b al-shay??n Min Kit?b al-Shajara in Terms of Reflecting Batıni Though - Gülmez, Cahit; Sürmeli, Zeynep Alimoğlu (Habip DEMİR, 2023)
B?b al-shay??n is a section within the book entitled by Kit?b al-Shajara Ab? Tamm?m, a member of Ism?iliyya. Ab? Tamm?m’s focuses on Kitab al-Shajara different creatures such as jinns, demons and humans, while B?b al-shay??n itself focuses on Islamic sects. The sect-associated identity of the author separates his work from other articles. B?b al-shay??n, one of two works authored by Ism?iliyya authors, reflects numerous esoteric elements. Furthermore, it has a unique classification system separating it from other articles. The book classifies Islamic sects into 73 divisions of hadiths. Ab? Tamm?m classifies these divisions under three main headings - those who consider Islamic practices a part of their belief, those who do not consider them to be so, and those who think imâmate is the right of Ali. He mentions 24 divisions under each heading. The 73rd division, known as Ahl al- B??in, came from Ab? Tamm?m. The objective of this article is to analyze the classification system of B?b al-shay??n, as well as the esoteric elements within the book so as to identify the place of this work among the other relevant articles and specify its unique traits.

Bâbü’ş-Şey?ân, İsmâiliyye mezhebine mensup Ebû Temmâm’ın Kitabüş-Şecere adlı eserinin bir bölümüdür. Kitabüş-Şecere’de cinler, şeytanlar, iblisler ve insanlar gibi çeşitli varlık türlerini inceleyen Ebû Temmâm, Bâbü’ş-Şey?ân’da ise İslam mezheplerine yer vermektedir. Müellifin mezhebî kimliği, eserini diğer makâlât eserlerinden farklı kılmaktadır. Zira İsmâilî müelliflerce kaleme alınmış iki eserden biri olan Bâbü’ş-Şey?ân’da pek çok bâtınî öge ile karşılaşmak mümkündür. Ayrıca eser kendisine has tasnif sistemiyle de diğer makâlât eserlerinden ayrılmaktadır. Eserde İslam mezhepleri yetmiş üç fırka hadisine göre tasnif edilmiştir. Amelleri imandan sayanlar, amelleri imandan saymayanlar ve imâmetin Hz. Ali’nin hakkı olduğunu düşünenler olmak üzere üç ana başlık altında fırkaları tasnif eden Ebû Temmâm, her başlık altında yirmi dört fırkaya yer vermiştir. Yetmiş üçüncü fırka ise Ebû Temmâm’ın Ehl-i Bâ?ın olarak nitelediği kendi fırkasıdır. Bu makalemizde amaç, Bâbü’ş-Şey?ân’ın başta tasnif sistemi ve bâtınî unsurların kullanımı olmak üzere diğer makâlât eserlerinden ayrılan özelliklerini tespit etmek olacaktır.
Bâtınî Düşünceyi Yansıtması Açısından Ebû Temmâm’ın Bâbü’ş-Şey?ân Min Kitabi’ş-Şecere Adlı Eserinin Tahlili
Keywords: Religious Studies; Din Araştırmaları